Microsurgical anatomy of the anterior approach to the mesial temporal region - Figueiredo, Eberval Gadelha; Teixeira, Manoel Jacobsen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2012)
Anterior approaches to the mesial temporal lobe are favored by its anatomy limited medially by the cerebral peduncle and laterally by the lateral temporal lobe. We have routinely used an anterior subfrontal approach to operate on mesial temporal lesions. In this paper, we describe its microsurgical anatomy and detail its clinical application. Surgical positioning, removal of the orbital rim, and drilling the sphenoid ridge are the main principles of this technique. Adequate positioning is crucial to displace the temporal lobe from the middle fossa to improve exposure. Removing the orbital rim ensures an ample range of movement for the surgical microscope, augments visualization, and improves surgical versatility. Finally, drilling the sphenoid ridge amplifies exposure near the area of interest, permitting increased visualization and manipulation.
Keywords: Microsurgical; temporal lobe; surgical procedures minimally invasive